Answer:
240
Step-by-step explanation:
Where P = pages and x = minutes, your rule is as follows:
[tex]P=\frac{10}{3} x[/tex]
Simply plug in your last minute value to find your last page value.
[tex]P=\frac{10}{3} (72)\\P=240[/tex]
4.4.45
For the following polynomial, one zero
is given. Find the remaining zeros.
The
(Sim
to se!
P(x) = x4 + 27x^2 - 324, 6i is a zero.
Answer:
[tex](x-6i)(x+6i)(x-3)(x+3)[/tex]
Step-by-step explanation:
If 6i is a zero then -6i is a zero.
In general, if a+bi is a zero then a-bi is a zero (if the polynomial has real coefficients which this one does: 1,27,-324).
Let's test it to see:
Check [tex]x=6i[/tex]
[tex]P(6i)=(6i)^4+27(6i)^2-324\\
P(6i)=6^4(i^4)+27(6)^2(i^2)-324\\
P(6i)=1296(1)+27(6^2)(-1)-324\\
P(6i)=1296-27(36)-324\\
P(6i)=1296-972-324\\
P(6i)=1296-1296\\
P(6i)=0\\[/tex]
Check [tex]x=-6i[/tex]
[tex]P(-6i)=(-6i)^4+27(-6i)^2-324\\
P(-6i)=(6i)^4+27(6i)^2-324\\
P(-6i)=P(6i)\\
P(-6i)=0\\[/tex]
So yep they both give us 0 when we plug it in.
If x=6i is a zero then x-6i is a factor by factor theorem.
If x=-6i is a zero then x+6i is a factor by factor theorem.
What is (x-6i)(x+6i)?
Let's use the multiply conjugates formula: [tex](u-v)(u+v)=u^2-v^2[/tex].
[tex](x-6i)(x+6i)=x^2-36i^2=x^2-36(-1)=x^2+36[/tex]
Now we know [tex](x^2+36)[/tex] is a factor of [tex]x^4+27x^2-324[/tex].
We can use long division or we could try to find two numbers that multiply to be -324 and add up to be 27 since this is a quadratic in terms of [tex]x^2[/tex] with leading coefficient of 1.
Well we already know we are looking for number times 36 that would give us -324.
So -324=-9(36) and 27=-9+36
So the factored form in terms of real numbers is:
[tex](x^2+36)(x^2-9)[/tex]
We already know the first factor can be factored as (x+6i)(x-6i).
The other can factored as (x-3)(x+3) since (-3)(3)=-9 and -3+3=0.
So the complete factored form is
[tex](x-6i)(x+6i)(x-3)(x+3)[/tex].
To find the remaining zeros of the polynomial, we use synthetic division and find a quadratic factor. The remaining zeros are the solutions to the quadratic equation x^2 + 9 = 0, which are 3i and -3i.
Explanation:To find the remaining zeros of the polynomial, we can use polynomial long division or synthetic division. Let's use synthetic division:
Since 6i is a zero of P(x), the conjugate -6i is also a zero. We can divide P(x) by (x - 6i)(x + 6i) to find the remaining quadratic factor.
Performing the synthetic division, we get a quadratic factor of x^2 + 9. Therefore, the remaining zeros of the polynomial are the solutions to the equation x^2 + 9 = 0.
Solving the quadratic equation x^2 + 9 = 0, we find that the remaining zeros are x = 3i and x = -3i.
Learn more about Polynomial zeros here:https://brainly.com/question/33963189
#SPJ11
what is an inequality? where would u use them in the real world
An inequality is comparing the relation of two equations that are not equal.
Depending on a persons cell phone plan, if they can only talk for so many minutes per month or send so many texts per month, this is an inequality written as number of minutes/ texts per month needs to be less than or equal to the allowable amount.
La suma de las edades de unos gemelos y unos trillizos es 150 años si se intercambian las edades la nueva suma es 120 años ¿ cual es la edad de los trillizos?
Answer:
The age of triplets is 42 years old
Step-by-step explanation:
The question in English is
The sum of the ages of twins and triplets is 150 years if the ages are exchanged the new sum is 120 years. What is the age of triplets?
Let
x -----> twins age
y ----> triplets age
we know that
2x+3y=150 ------> equation A
2y+3x=120 -----> equation B
Solve the system by graphing
The intersection point both graphs is the solution of the system
The solution is the point (12,42)
see the attached figure
therefore
The age of triplets is 42 years old
EXPLAIN!!!!!!!!!!!!!!
Answer:
111
Step-by-step explanation:
because the lines are parallel and they are on opposite sides its like having two angles on the same line but on different sides so they are supplementary meaning they add up to 180 and 180-69 = 111
please mark brainliest :)
Which statement is true about lines a and b?
They are parallel lines.
They are perpendicular lines.
They are skew lines.
They will intersect.
It would be C. they are skew on ED :)
Answer: C
Step-by-step explanation: your welcome
finding whole number equal to fraction 8/1
Answer: 8
Step-by-step explanation: 8 divided by 1 is 8
8 is the whole number equal to fraction 8/1.
What is Number system?A number system is defined as a system of writing to express numbers.
The given fraction is 8/1
Eight divided by one.
A fraction represents a part of a whole or, more generally, any number of equal parts.
8 is the numerator and 1 is the denominator.
The complete set of natural numbers along with '0' are called whole numbers.
If a number is divided by another number then the result will be the numerator which is whole number.
8/1=8
Hence, 8 is the whole number equal to fraction 8/1.
To learn more on Number system click:
https://brainly.com/question/22046046
#SPJ2
You are choosing 3 of your 7 trophies and arranging them in a row on a shelf.
In how many different ways can you choose and arrange the trophies?
Answer:
21
Step-by-step explanation:
you can arrange 7×3 ways
Answer with explanation:
Number of trophies possessed by me= 7
Number of trophies that is to be selected from 7 trophies =3
⇒⇒So, Chosing 3 out of 7 trophies and arranging them on a shelf requires Concept of Permutation, as order of arrangement is also taken into consideration
[tex]=_{3}^{7}\textrm{P}\\\\=\frac{7!}{(7-3)!}\\\\=\frac{7!}{4!}\\\\=\frac{4!*5*6*7}{4!}\\\\=5*6*7\\\\=210\text{Ways}[/tex]
Or
⇒First place can be filled in 7 ways,second place can be filled in 6 ways and third place can be filled in 5 ways.
So total number of ways of selecting 3 trophies from 7 trophies
=7 *6 *5
=210 ways
⇒Now, 3 trophies can be arranged in a shelf in 3! =3 *2*1=6 ways.
There are 22 participants in a spelling bee. In how many ways can the top 5 participants finish? Use the formula for permutations to find your answer
Answer:
3,160,080Explanation:
The formula for permuations is nPk:
[tex]_nP_k=\frac{n!}{(n-k)!}=(n)(n-1)(n-2)...(n-k+1)[/tex]Where n is the total number of elements from which you must choose combinations of k number of elements, and where the order of selection is relevant.
In this case n = 22 (the number of participants), k = 5 (the number of top participants). Since, the order in which the participants finish is relevant, then you have to use the formula of permutations, such as the question states.
Calculations:
[tex]_{22}P_5=\frac{22!}{(22-5)!}=22.21.20.19.18=3,160,080[/tex]The function F(c) = 9/5 c + 32 allows you to
Answer:
convert from Celsius to Fahrenheit
Step-by-step explanation:
i work with thermometers i know
For this case we have that by definition, to convert degrees Celsius to Fahrenheit we use the following formula:
[tex]F = \frac {9} {5} C + 32[/tex]
Where:
C: Represents the degrees Celsius
So, we can write a function:
[tex]F (C) = \frac {9} {5} C + 32[/tex]
Answer:
The function allows to convert degrees Celsius to Fahrenheit
4 times the sun q and p
Typo is probably in "sun" being really "sum".
Just write an equation.
[tex]4(q+p)=4q+4p[/tex]
Hope this helps.
r3t40
Determine the area and perimeter of figure described:
square with sides of length 9mm
Answer:
Perimeter= 36mm
Area= 81mm
Step-by-step explanation:
raph the equation with a diameter that has endpoints at (-3, 4) and (5, -2). Label the center and at least four points on the circle. Write the equation of the circle.
Answer:
Equation:
[tex]{x}^{2} + {y}^{2} + 2x - 2y - 35= 0[/tex]
The point (0,-5), (0,7), (5,0) and (-7,0)also lie on this circle.
Step-by-step explanation:
We want to find the equation of a circle with a diamterhat hs endpoints at (-3, 4) and (5, -2).
The center of this circle is the midpoint of (-3, 4) and (5, -2).
We use the midpoint formula:
[tex]( \frac{x_1+x_2}{2}, \frac{y_1+y_2,}{2} )[/tex]
Plug in the points to get:
[tex]( \frac{ - 3+5}{2}, \frac{ - 2+4}{2} )[/tex]
[tex]( \frac{ -2}{2}, \frac{ 2}{2} )[/tex]
[tex]( - 1, 1)[/tex]
We find the radius of the circle using the center (-1,1) and the point (5,-2) on the circle using the distance formula:
[tex]r = \sqrt{ {(x_2-x_1)}^{2} + {(y_2-y_1)}^{2} } [/tex]
[tex]r = \sqrt{ {(5 - - 1)}^{2} + {( - 2- - 1)}^{2} } [/tex]
[tex]r = \sqrt{ {(6)}^{2} + {( - 1)}^{2} } [/tex]
[tex]r = \sqrt{ 36+ 1 } = \sqrt{37} [/tex]
The equation of the circle is given by:
[tex](x-h)^2 + (y-k)^2 = {r}^{2} [/tex]
Where (h,k)=(-1,1) and r=√37 is the radius
We plug in the values to get:
[tex](x- - 1)^2 + (y-1)^2 = {( \sqrt{37}) }^{2} [/tex]
[tex](x + 1)^2 + (y - 1)^2 = 37[/tex]
We expand to get:
[tex] {x}^{2} + 2x + 1 + {y}^{2} - 2y + 1 = 37[/tex]
[tex]{x}^{2} + {y}^{2} + 2x - 2y +2 - 37= 0[/tex]
[tex]{x}^{2} + {y}^{2} + 2x - 2y - 35= 0[/tex]
We want to find at least four points on this circle.
We can choose any point for x and solve for y or vice-versa
When y=0,
[tex]{x}^{2} + {0}^{2} + 2x - 2(0) - 35= 0[/tex]
[tex]{x}^{2} +2x - 35= 0[/tex]
[tex](x - 5)(x + 7) = 0[/tex]
[tex]x = 5 \: or \: x = - 7[/tex]
The point (5,0) and (-7,0) lies on the circle.
When x=0
[tex]{0}^{2} + {y}^{2} + 2(0) - 2y - 35= 0[/tex]
[tex] {y}^{2} - 2y - 35= 0[/tex]
[tex](y - 7)(y + 5) = 0[/tex]
[tex]y = 7 \: or \: y = - 5[/tex]
The point (0,-5) and (0,7) lie on this circle.
3) Find the length of a rectangular lot with a perimeter of 92 m if the length is 8 m more than
the width.
Answer:
26 m
Step-by-step explanation:
Perimeter = 92 m
Length = 8 m more than width
Width: 20 m
Therefore,
length=26 mThe width of the rectangular lot is 19 m and the length is 27 m.
Explanation:The subject of this question is the calculation of the length of a rectangular lot. The perimeter of a rectangle is the sum of all its sides, given by the formula 2*(length + width). From the question, we know that the perimeter is 92 m, and the length is 8 m more than the width. Suppose 'w' is the width. Thus the length is 'w + 8' m.
So, we can set up the equation 2*(w + w + 8) = 92. Solving this equation will give us the value for the width (w) and consequently, the length by adding 8 to it.
Step-by-step solution:Combine like terms on the left side to get 2*(2w + 8) = 92.Then, distribute 2 to get 4w + 16 = 92.Subtract 16 from both sides to have 4w = 76.Finally, divide by 4 to find w = 19 m.The length (w+8) will then be 19m + 8m = 27m.Learn more about Rectangular Lot Dimensions here:https://brainly.com/question/34270507
#SPJ2
Solve for x.
A. 2
B. 4
C. 6
D. 8
The full length of one line times the length of the line outside the circle is equal the the other line.
(x-1) +5 x 5 = (2+x)+4 x 4
Simplify:
(x+4) x 5 = (x +6) x 4
5x +20 = 4x +24
Subtract 20 from each side:
5x = 4x +4
Subtract 4x from each side:
x = 4
The answer is B. 4
When you multiply a function by -1, what is the effect on its graph?
Step-by-step explanation:
[tex]\dfrac{a}{b}\cdot(-1)=-\dfrac{a}{b}[/tex]
On the number line, fractions a/b and -a/b lie on the opposite sides of the number 0, at the same distance (look at the picture).
Everyday there are 4 times more like on an internet video of a horse which is modeled by the function c(n)=(4)^n-1 where n is the number of day since the video posted on the first day there were 100 likes what is the function that shows the number of likes each day
Answer:
Step-by-step explanation:
A better way to write the first function would be:
c(n) = 4*c(n-1), meaning that the number of likes is equal to four times the number of likes from the previous day.
On the first day, c(n)=c(0) = 100
Therefore:
C(n) = 100 * 4^n
Let's plug in a view values to test our function:
When n= 0 (first day)
C(0) = 100 * 4 ^0 = 100*1 = 100 likes
C(1) = 100 * 4^1 = 100 * 4 = 400 likes, four times the previous day
C(2) = 100 * 4^2 = 100 * 16 = 1600 likes, four times the previous day
And so on. Our function is an accurate descriptor of the model.
Type the correct answer in the box. For this item, any non-integer answer should be entered as a decimal rounded to the hundredths place. Statistics show that a certain soccer player has a 63% chance of missing the goal each time he shoots. If this player shoots twice, the probability that he scores a goal both times is_____ %.
Answer:
13.69%.
Step-by-step explanation:
The probability he scores in 1 shot = 1 - 0.63 = 0.37.
The probability that he scores twice in 2 shots = 0.37 * 0.37
= 0.1369
= 13.69%.
The probabilities are multiplied because the 2 events are independent.
Answer:
For plato user the answer is 13.69 %.
Step-by-step explanation:
If this player shoots twice, the probability that he scores a goal both times is
13.69 %.
Select the equation of the line parallel to the equation 2x + 4y = -5 that passes through the point (-4, -8).
a). x + 2y = 16
b). 2x + y = -16
c). 2x + 4y = -9
d). x + 2y = -20
Answer:
D.
Step-by-step explanation:
First, put your original equation in slope-intercept form to find your slope.
[tex]y=mx+b\\2x+4y=-5\\4y=-2x-5\\y=-\frac{1}{2} x-\frac{5}{4}[/tex]
Now that you have your slope ([tex]-\frac{1}{2}[/tex]) and a point, you can use point-slope form to find your y-intercept.
[tex]y-y1=m(x-x1)\\y-(-8)=-\frac{1}{2} (x-(-4))\\y+8=-\frac{1}{2} (x+4)\\y+8=-\frac{1}{2} x-2\\y=-\frac{1}{2} x-10[/tex]
Your answer choices are all in [tex]Ax+By=C[/tex] form, so lets convert our equation into that form.
[tex]y=-\frac{1}{2} x-10\\1/2x+y=-10\\x+2y=-20[/tex]
If we multiply all of our terms by 2, we can get answer choice D.
Find the center and radius of the circle (x+3)^2+(y-1)^2=81
The equation of a circle is written as ( x-h)^2 + (y-k)^2 = r^2
h and k is the center point of the circle and r is the radius.
In the given equation (x+3)^2 + (y-1)^2 = 81
h = -3
k = 1
r^2 = 81
Take the square root of both sides:
r = 9
The center is (-3,1) and the radius is 9
If $125 is invested at an interest rate of 18% per year and is compounded continuously, how much will the investment be worth in 2 years? Use the continuous compound interest formula A=Pe^rt
Answer:
$179.17
Step-by-step explanation:
https://brainly.com/question/12714871
Answer: The investment be worth $ 174.05 in 2 years .
Step-by-step explanation:
Given : The principal amount invested : A= $125
Interest rate : r = 18% =0.18 [ Percent convert into decimal if we divide it by 100]
Time : t = 2 years
The formula to find the accumulated amount if compounded continuously :-
[tex]A=Pe^rt\\\\=(125)(1+0.18)^{2}\\\\= 125 (1.18)^2\\\\ = 125 (1.3924)\\\\=174.05[/tex]
Hence, the investment be worth $ 174.05 in 2 years .
25. Tom and Jerry must stuff and mail 1000
envelopes for a new marketing campaign. Jerry
can do the job alone in 6 hours. If Tom helps,
they can get the job done in 4 hours. How long
would it take Tom to do the job by himself?
A. 4 hours
B. 5 hours
C. 8 hours
D. 12 hours
Answer:
12
Step-by-step explanation:
The general formula for this is
Formula
1/t1 + 1/t2 = 1/t_tot
givens
t1 = 6 hours
t2 = x
t_tot = 4 hours
Solution
1/6 + 1/x = 1/4 Subtract 1/6 from both sides.
1/6-1/6 + 1/x = 1/4 - 1/6 Change to 12 as your common denominator
1/x = 3/12 - 2/12 subtract
1/x = 1/12 Cross multiply
x = 12
Tom would need 12 hours to do the job alone.
Answer:
Option D. 12 hours
Step-by-step explanation:
Let the work done by Tom to do the job alone = x hours
So per hour work done by Tom = [tex]\frac{1}{x}[/tex]
Jerry can do the job alone in the time = 6 hours
Per hour work done by Jerry = [tex]\frac{1}{6}[/tex]
Similarly job done by both together in the time = 4 hours
Per hour work done by both together = [tex]\frac{1}{4}[/tex]
Now we know,
Per hour work done by both together = per hour work done by Tom + Per hour work don by Jerry
[tex]\frac{1}{4}=\frac{1}{x}+\frac{1}{6}[/tex]
[tex]\frac{1}{x}=\frac{1}{4}-\frac{1}{6}[/tex]
[tex]\frac{1}{x}=\frac{3-2}{12}[/tex]
[tex]\frac{1}{x}=\frac{1}{12}[/tex]
x = 12 hours
Option D. will be the answer.
4,792÷8 show your work
Answer:
4,792 ÷ 8 = 599Step-by-step explanation:
Look at the picture.
Use the long division.
WILL GIVE BRAINLEST SUPER EASY A coyote can run up to 43 miles per hour while a rabbit can run up to 35 per hour. Write two equivalent expressions and then find how many more miles a coyote can run in six hours than a rabbit at these rates.
48 more miles
Coyote= 43h
Rabbit= 35h
Coyote= 43(6)= 258
Rabbit= 35(6)= 210
Now subtract 258 by 210
258-210= 48
please Answer fast .......
Answer:
Option 3 [tex]\frac{67}{441}[/tex]
Step-by-step explanation:
step 1
Find the roots of the quadratic equation
we have
[tex]3x^{2}+5x-7=0[/tex]
The formula to solve a quadratic equation of the form [tex]ax^{2} +bx+c=0[/tex] is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]3x^{2}+5x-7=0[/tex]
so
[tex]a=3\\b=5\\c=-7[/tex]
substitute in the formula
[tex]x=\frac{-5(+/-)\sqrt{5^{2}-4(3)(-7)}} {2(3)}[/tex]
[tex]x=\frac{-5(+/-)\sqrt{109}} {6}[/tex]
[tex]x=\frac{-5+\sqrt{109}} {6}[/tex]
[tex]x=\frac{-5-\sqrt{109}} {6}[/tex]
step 2
Let
[tex]\alpha=\frac{-5+\sqrt{109}} {6}[/tex]
[tex]\beta=\frac{-5-\sqrt{109}} {6}[/tex]
we need to calculate
[tex]\frac{1}{(3\alpha+5)^{2}}+ \frac{1}{(3\beta+5)^{2}}[/tex]
step 3
Calculate [tex](3\alpha+5)^{2}[/tex]
[tex](3\alpha+5)^{2}=[3(\frac{-5+\sqrt{109}} {6})+5]^{2}[/tex]
[tex]=[(\frac{-5+\sqrt{109}} {2})+5]^{2}[/tex]
[tex]=[(\frac{-5+\sqrt{109}+10} {2})]^{2}[/tex]
[tex]=[(\frac{5+\sqrt{109}} {2})]^{2}[/tex]
[tex]=[(\frac{25+10\sqrt{109}+109} {4})][/tex]
[tex]=[(\frac{134+10\sqrt{109}} {4})][/tex]
[tex]=[(\frac{67+5\sqrt{109}} {2})][/tex]
step 4
Calculate [tex](3\beta+5)^{2}[/tex]
[tex](3\beta+5)^{2}=[3(\frac{-5-\sqrt{109}} {6})+5]^{2}[/tex]
[tex]=[(\frac{-5-\sqrt{109}} {2})+5]^{2}[/tex]
[tex]=[(\frac{-5-\sqrt{109}+10} {2})]^{2}[/tex]
[tex]=[(\frac{5-\sqrt{109}} {2})]^{2}[/tex]
[tex]=[(\frac{25-10\sqrt{109}+109} {4})][/tex]
[tex]=[(\frac{134-10\sqrt{109}} {4})][/tex]
[tex]=[(\frac{67-5\sqrt{109}} {2})][/tex]
step 5
substitute
[tex]\frac{1}{(3\alpha+5)^{2}}+ \frac{1}{(3\beta+5)^{2}}[/tex]
[tex]\frac{1}{[(\frac{67+5\sqrt{109}} {2})]}+ \frac{1}{[(\frac{67-5\sqrt{109}} {2})]}[/tex]
[tex]\frac{2}{67+5\sqrt{109}} +\frac{2}{67-5\sqrt{109}}\\ \\\frac{2(67-5\sqrt{109})+2(67+5\sqrt{109})}{(67+5\sqrt{109})(67-5\sqrt{109})} \\ \\\frac{268}{1764}[/tex]
Simplify
Divide by 4 both numerator and denominator
[tex]\frac{268}{1764}=\frac{67}{441}[/tex]
Answer:
3) 67/441
Step-by-step explanation:
Comparing the given equation to the expressions you need to evaluate, you find there might be a simplification.
3x² +5x -7 = 0 . . . . . given equation
3x² +5x = 7 . . . . . . . add 7
x(3x +5) = 7 . . . . . . . factor
3x +5 = 7/x . . . . . . . . divide by x
Now, we can substitute into the expression you are evaluating to get ...
1/(3α +5)² +1/(3β +5)² = 1/(7/α)² +1/(7/β)² = (α² +β²)/49
__
We know that when we divide the original quadratic by 3, we get
x² +(5/3)x -7/3 = 0
and that (α+β) = -5/3, the opposite of the x coefficient, and that α·β = -7/3, the constant term. The sum of squares is ...
α² +β² = (α+β)² -2αβ = (-5/3)² -2(-7/3) = 25/9 +14/3 = 67/9
Then the value of the desired expression is ...
(67/9)/49 = 67/441
Solve the system of equation and choose the correct ordered pair.!2x-6y=8 5x-4y=31
Answer:
The correct ordered pair is (7,1)
Step-by-step explanation:
The given system has equations:
[tex]2x - 6y = 8....(1)[/tex]
[tex]5x- 4y = 31....(2)[/tex]
We make x the subject in the first equation to get:
[tex]x = 4 + 3y...(3)[/tex]
Put equation 3 into equation 2 to get:
[tex]5(4 + 3y) - 4y = 31[/tex]
Expand:
[tex]20 + 15y - 4y = 31[/tex]
[tex]15y - 4y = 31 - 20[/tex]
[tex]11y = 11[/tex]
[tex]y = 1[/tex]
Put y=1 into equation 3 and solve for x.
[tex]x = 4 + 3( 1) = 7[/tex]
The correct ordered pair is (7,1)
PLEASE ANSWER 9 and 10
GEOMETRY SOLVING FOR MISSING ANGLE
Answer:
9. 75°
10. 60°
Step-by-step explanation:
Note the angle-intercept theorem. If you create an angle in the opposite side of a circle from 2 points on other side, the arc will have a measure TWICE that of the intercepted angle created on other side.
Question 9
Arc WX has a measure 76, thus the angle created is Angle V, which should be HALF of that. So angle V is 76/2 = 38
Now looking at the triangle inside the circle, we know three angles of a triangle add up to 180, thus we can write and solve for "?" angle:
X + W + V = 180
? + 67 + 38 = 180
? + 105 = 180
? = 180 - 105 = 75°
Question 10
Using the theorem we can say that Angle B is HALF of ARC XYZ.
So,
2*Angle B = Arc XY + Arc YZ
2*102 = Arc XY + 124
204 = Arc XY + 124
Arc XY = 204 - 124 = 80°
Also, Arc BX + Arc XY is twice that of Angle Z (which is 70), thus
Arc BX + Arc XY = 70 *2
Arc BX + Arc XY = 140
Arc BX + 80 = 140
Arc BX = 140 - 80 = 60°
The phosphate groups that are the polar of the phospholipid because they are A.charged B. Neutral C. Hydrophilic D. hydrophobic
Answer:
The phosphate groups that are the polar of the phospholipid because they are charged - A.
The phosphate groups that are the polar of the phospholipid because they are A. charged
What is phospholipid?It is group of polar lipids that consist of two fatty acids , a glycerol unit and a phosphate group .
A phosphate group has a negatively charged oxygen and a positively charged nitrogen to make this group ionic. A single phospholipid molecule has a phosphate group on one end and two chains of fatty acids . The phosphate group is negatively charged making the head polar and hydrophilic .
correct answer A) charged
learn more about phospholipid
https://brainly.com/app/ask?q=phospholipid
#SPJ2
Give the equation for a circle with the given center and radius.
Center at (4, 1), radius = 6
Answer:
(x-4)^2 + (y-1)^2 = 6^2
or
(x-4)^2 + (y-1)^2 = 36
Step-by-step explanation:
The equation for a circle is given by
(x-h)^2 + (y-k)^2 = r^2
where (h,k) is the center and r is the radius
(x-4)^2 + (y-1)^2 = 6^2
or
(x-4)^2 + (y-1)^2 = 36
Answer:
(x - 4)^2 + (y - 1)^2 = 6^2
Step-by-step explanation:
Adapt the standard equation of a circle with center at (h, k) and radius r:
(x-h)^2 + (y-k)^2 = r^2
Here we have:
(x - 4)^2 + (y - 1)^2 = 6^2
what is the equation of a line that contains the point (2,-5) and is parallel to the line y=3x-4
Answer:
y = 3x - 11
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
y = 3x - 4 ← is in slope- intercept form
with slope m = 3
• Parallel lines have equal slopes, hence
y = 3x + c ← is the partial equation of the parallel line
To find c substitute (2, - 5) into the partial equation
- 5 = 6 + c ⇒ c = - 5 - 6 = - 11
y = 3x - 11 ← equation of parallel line
the equation of the line that is parallel to y = 3x - 4 and passes through the point (2, -5) is:
y = 3x - 11To find the equation of a line that is parallel to a given line and passes through a certain point, we need to use the concept that parallel lines have the same slope. The slope-intercept form of a line's equation is y = mx + b, where m is the slope and b is the y-intercept. Given that the line is parallel to y = 3x - 4, it will have the same slope, which is 3. Thus the slope of our new line is also 3.
We want our line to pass through the point (2, -5). Plugging these values into the slope-intercept form, we get:
-5 = 3(2) + bwhich simplifies to:
-5 = 6 + bThus, the y-intercept b of our new line is:
-5 - 6 = bTherefore, the equation of the line that is parallel to y = 3x - 4 and passes through the point (2, -5) is:
y = 3x - 1137. Two years ago, Bob flew 6 x 105 miles in an airplane. This was 15 times as many
miles as he flew last year.
How many miles did Bob fly last year?
A. 4* 104 miles
B. 4 x 106 miles
C. 9 x 104 miles
D. 9 * 106 miles
Answer:
A. 4·10⁴
Step-by-step explanation:
The problem statement tells you ...
6×10⁵ miles = 15 × (last year's mileage)
Dividing by 15 gives ...
(60×10⁴ miles)/15 = (last year's mileage) = 4×10⁴ miles
_____
Further explanation
An exponent is an indication of repeated multiplication.
10⁵ = 10·10·10·10·10 = 100,000
We can use the associative property of multiplication to rewrite the number of miles:
6×10⁵ = 6·(10·10·10·10·10) = 600,000 = (6·10)·(10·10·10·10) = 60×10⁴